Respostas da Tilápia do Nilo (Oreochromis niloticus) à Atratividade e Palatabilidade de Ingredientes Utilizados na Alimentação de Peixes - Pereira-Da-Silva, Elyara Maria; Pezzato, Luiz Edivaldo [UNESP] (My University, 2000)
The response of Nile tilapia to the attraction and palatability of 14 ingredients was evaluated. The two-choice method was used, comparing each pelleted ingredient to acontrol diet. It was utilized Four aquaria (750 liters) containing in each one three fingerlings and two feed containers at the right and left corner, being recorded the elapsed time between the lay of the ingredient and the arrive of the fingerlings to feed containers, visiting frequency to the feed containers, amount of ingested pellets and ejections frequency. The treatments were compared by non-parametric method of Kruskal-Wallis and the comparison of the ingredients for the variable set using Grouping Analysis and Principal Components Analysis. The numbers of ingested pellets (at morning and at afternoon) and the visiting frequency to feed containers (at afternoon) were considered the most discriminatory variables. The ingredients were classified as it follows: a) low attraction and palatability = wheat meal, soybean meal, cottonseed meal, cassava meal, cassava scrapings, sunflower meal and corn meal), b) medium attraction and palatability = sugar-cane yeast and corn gluten meal and c) high attraction and palatability = integral lyophilized egg, silk worm meal, fish meal, meat meal, shrimp meal. The frequency of ejected pellets and time spent to approach of the feed (at morning and at afternoon) were considered the least discriminatory variables. The behavior response of fishes changes according to the presented ingredient. The attraction and palatability extent must be studied considering combinations of variables.
Response of Nile Tilapia (Oreochromis niloticus) to the Attraction and Palatability of the Used Ingredients in the Feeding of Fishes
Keywords: Attraction; Ingredient; Nile tilapia; Oreochromis niloticus; Palatability